Communication Strategy of Community Health Center’ Cadres in Preventing Stunting - T. Mardiansyah (Universitas Teuku Umar, 2022)
Stunting is one of the five focuses of health problems that must be solved in Indonesia, this study aims to analyze the communication strategy of the Posyandu Cadre in Puuk Village in an effort to prevent stunting using quantitative methods. Data was collected by distributing questionnaires to 30 people in Puuk Village, then the data were analyzed by tabulation and scored and then explained descriptively. There are two sources of data, namely primary data by observing and distributing questionnaires and secondary data obtained from related institutions, books, journals or articles related to the research conducted. The focus studied on posyandu cadres will focus on communication strategies which include techniques, approaches, channels and communication messages. The results of this study are indicators of communication techniques on high criteria, indicators of communication approaches on medium criteria, on communication channel indicators on medium criteria and finally on indicators of communication messages on high criteria.